PENGARUH VARIASI PARAMETER PROSES PEMESINAN TERHADAP GAYA POTONG PADA MESIN BUBUT KNUTH DM-1000A - Stella Daran Hindom; Rudy Poeng; Romels C A Lumintang (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2015)
This research was aimed at knowing the cutting force a lathe with several parameters: rotation condition,varied cutting depth,and constant eater motion. The influence of the machining parameters to the cutting forcewas obtained by conducting tests on KNUTH DM 1000 A lathe.on every test with changing rotation and cutting depth, the electric current can be measured with ampere pliers. From the data of the electric currenst, the power and cutting force of every test can be calculated. From the test result and interacted two way variance analysis,it was found that the most influential parameters to the cutting force is the rotation,while the cutting depth does not influential the cutting force significantly, so it can be ignored. On 300 rpm gave the average cutting force of 2166 N, on 700 rpm 918 N,and on 1600 rpm. This results show that the rotation, the lower the cutting force. Keywords : lathe, machining parameters, cutting force